Prolonged QTc Dispersion Correlates with Coronary Artery Disease in Acute ST Elevated Myocardial Infarction (STEMI) (Cardiovascular Journal, 2013)
Background: It has been found that there is strong association of QT dispersion and QT dispersion ratio with extent and severity of coronary artery disease. Qualitative importance of QTc dispersion on the base line ECG in patients with MI is recognized clinically but quantification of this phenomenon is less commonly used in clinical practice, which might be a better independent risk predictor of this group of patients. Methods: A total of 100 patients were selected, Study populations sub-divided into two groups on the basis of QTc dispersion. In group I (comparison group): QTc dispersion is